EFEKTIVITAS MODEL PEMBELAJARAN CARD SORT UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA IPAS KELAS V DI SD KARANGMOJO - Nurfadhilah, Alifah Aulia (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
This study focuses on evaluating the effectiveness of the Card Sort learning model on students' academic achievement at Karangmojo Elementary School. The research design employed a quantitative approach, involving 20 students as the sample, measured before (pretest) and after (posttest) the implementation of the Card Sort model. Data analysis was conducted in two stages: a normality test using the Kolmogorov–Smirnov method, followed by a paired sample t-test. The normality test results indicated that both the pretest (Asymp. Sig. 0.200) and posttest (Asymp. Sig. 0.194) scores were normally distributed (p > 0.05), thus meeting the assumptions for parametric testing. Descriptively, there was an increase in the average score from the pretest (60.30) to the posttest (67.40). The paired sample correlation analysis indicated a significant positive relationship between the pretest and posttest scores (r = 0.539, p = 0.014). However, the paired sample t-test showed that the difference in mean scores between the pretest and posttest was not statistically significant (t = −1.834, df = 19, p = 0.082). Although there was an increase in scores, the lack of statistical significance (p > 0.05) suggests that the Card Sort learning model did not significantly improve student achievement at Karangmojo Elementary School in this study.